2014
DOI: 10.3390/toxins6092657
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hydrogen Peroxide to the Control of Eutrophic Lake Systems in Laboratory Assays

Abstract: We exposed water samples from a recreational lake dominated by the cyanobacterium Planktothrix agardhii to different concentrations of hydrogen peroxide (H2O2). An addition of 0.33 mg·L−1 of H2O2 was the lowest effective dose for the decay of chlorophyll-a concentration to half of the original in 14 h with light and 17 h in experiments without light. With 3.33 mg·L−1 of H2O2, the values of the chemical oxygen demand (COD) decreased to half at 36 and 126 h in experiments performed with and without light, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…Hydrogen peroxide is effective in freshwater at low concentration (≈3 mg L −1 ) (Bauzá et al . ). Microcystis toxins (microcystins) are considered hepatotoxic, whereas anatoxin‐a (produced by Anabaena spp.)…”
Section: Chemical and Physical–chemical Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hydrogen peroxide is effective in freshwater at low concentration (≈3 mg L −1 ) (Bauzá et al . ). Microcystis toxins (microcystins) are considered hepatotoxic, whereas anatoxin‐a (produced by Anabaena spp.)…”
Section: Chemical and Physical–chemical Methodsmentioning
confidence: 97%
“…As advantage over other algicidals, hydrogen peroxide destroys microcystins helped by natural UV radiation (Bauzá et al . ). Similarly, photocatalytic degradation of microcystins is also possible (Shephard et al .…”
Section: Chemical and Physical–chemical Methodsmentioning
confidence: 97%
“…However, many studies only examined H 2 O 2 toxicity in the MC-producing species from Planktothrix and Microcystis genera. Much less is known on the interspecific variation across other common bloom-forming and potentially toxic cyanobacteria from the genera Dolichospermum, Aphanizomenon, or Raphidiopsis, however a wide range of H 2 O 2 toxicity thresholds against these cyanobacteria have been documented [22][23][24]. The current study has shown different responses of cyanobacteria to the treatment, depending on the stage of the experiment.…”
Section: Treatment In Lake Ludošmentioning
confidence: 60%
“…Nevertheless, the use of copper sulfate is not the only option for water quality management (Beaulieu et al, 2005;Huh and Ahn, 2017). Other effective methods for the control of algae and cyanobacteria include the use of hydrogen peroxide, which is associated with fewer longterm ecotoxicological impacts (Matthijs et al, 2012;Bauzá et al, 2014;Lürling et al, 2014).…”
Section: Introductionmentioning
confidence: 99%